Compendium of International and National Legal Frameworks on Domestic Violence - World Bank (World Bank, Washington, DC, 2019)
Domestic Violence (DV) is a universal phenomenon that affects millions of women of all social strata worldwide. It is the most pervasive, common, under-recognized, underestimated and under-reported type of violence against women. It reflects discriminatory social norms, stereotypes, impunity and gender inequality. It is all too often considered as a “private, family issue”, widely accepted and minimized although it impairs the full enjoyment of life and fundamental rights and freedoms by victims and survivors who are overwhelmingly women. Domestic Violence (DV) is a development challenge and has a high economic and social cost, including health and medical costs, death, suicide, depression, lost productivity, lost income, , psychological consequences and trauma, increased stress, reactive violence, reduced ability to study or find and hold a job, judicial and prison costs, economic insecurity and abuse, debt, housing instability, homelessness, inter alia1. Beyond data and statistics, DV undermines autonomy and represents an enormous loss in terms of wellbeing not only for the women affected but also for the men who share their lives, for their children, their families and their societies. The Compendium on International and National Legal Frameworks on Domestic Violence (the “Compendium”) provides a survey of the key international and regional instruments as well as national legislation as they relate to domestic violence.